A Comparative Study of Skepticism Towards Triumph in the Search for Truth Imam Al-Ghazali in Al-Munqidz min Al-Dhalal and Sophie in Sophie's World - Al Hallaji, Ahmad; Affandi, Achmad Lutfi; Setiani, Wiwik; Riyadi, Abdul Kadir (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to compare the dynamics of the search for truth experienced by Imam al-Ghazali in his autobiographical work Al-Munqidh min al-Dhalal and the fictional character Sophie in Jostein Gaarder’s novel Sophie's World. The theme of the search for truth is significant as it reflects the intellectual and spiritual struggles of human beings across time and cultures, offering deep reflections on the crisis of meaning often found in modern life. Using a qualitative approach and content analysis method, this research examines the stages both figures undergo—facing skepticism, engaging in critical reflection, and ultimately attaining philosophical and spiritual conviction. Imam al-Ghazali experienced an epistemological crisis that led him to the path of Sufism as a means of achieving certainty, while Sophie embarks on a rational journey through philosophical dialogues toward existential understanding. The findings show that, despite originating from different historical and intellectual traditions, both figures follow a similar pattern in their quest for truth: intellectual unrest, distrust of external authority, pursuit of independent thinking, and the eventual discovery of a personal and transformative form of belief. These findings highlight the importance of dialogue between Eastern spiritual traditions and Western philosophy in understanding the dynamics of truth-seeking in today’s global and contemporary context.